Comparative Analysis of Meshing Characteristics Between Point-line Meshing Gears and Involute Gears - Tang Yu; Chang Shan; Yang Long; Wang Zhiqiang (Jixie chuandong)
Taking point-line meshing gears and involute gears as the research object, a simulation model of two kinds of meshing gears is established, the meshing characteristics of point-line meshing gears and involute gears in transmission error, tooth surface load distribution, tooth surface sliding speed distribution, tooth surface contact stress distribution, tooth root bending stress distribution, meshing contact trace analysis are comprehensively compared and analyzed. It is obtained that the point-line meshing gear is obviously better than the involute gear in the above meshing characteristics, which provides a theoretical basis for a more comprehensive understanding of point-line meshing gear transmission and has a certain theoretical value for its popularization and application.